POVERTY ALLEVIATION PROGRAMMES AND THE PREVAILING CHALLENGES FOR SUSTAINABLE DEVELOPMENT GOALS IN NIGERIA: AN ASSESSMENT - `WOYINMO TIMI AMAKOROMO; VICTOR IHEANYICHUKWU ASIEGBU; CELESTINE OGECHUKWU OKAFOR (International Studies Journal)
Strategic planning and implementation of well thought out policies is critical for the enthronement of good governance which brings about sustainable development in any country. However, available data shows that poverty is steadily on the rise in Nigeria, despite the country’s effort in the implementation of diverse poverty alleviation programmes. Thus, such a worrisome trajectory appears to be linked to so many factors such as corruption, debt burden, rising rate of unemployment especially among youths, overdependence on oil, lack of political will to address poverty, ethno-religious conflicts among others. It argued that efforts to alleviate poverty through poverty alleviation programmes will remain an exercise in futility without first addressing fundamental, societal hiccups like corruption, economic inequality and ethno-religious conflicts. Methodologically, this study adopted documentary method while relying on content qualitative content analysis to analyze data gathered. The study likewise utilized abstractions from the theory of post-colonial state which served as its theoretical framework of analysis. Findings showed that unless selfless and responsible political leadership is entrenched in Nigeria, which would lead to tackling fundamental problems associated with income inequality, corruption, political instability and other related vices in the Nigerian society, the fight against poverty may remain unresolved and the search for sustainable development will continue to be a mirage. The study therefore, recommended among others that the government should first address societal hiccups to the success of poverty alleviation programmes, such as economic inequality, ethno-religious conflicts and corruption. This will engender a fair and favourable playground for the poverty alleviation progrmames to thrive and be successful.